The duality of cuIture in Iuri Lotman's work - Wahnón, Sultana (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
This paper attempts to delimit the place that would occupy Lotman's theory of culture in relation to modern philosophy. For this purpose, it considers as its central ideas, in first place, the role of art in racionalist societies, and, in second place, the philosophy of history, or, rather, that which receives that name, that is, the Hegelian philosophy of history. The paper emphasizes, on the one hand -and opposite to racionalist unconcem about art's truth-, Lotman's valuation of the literary art's truth or content; on the other hand, it underlines the difference between Lotman's concept of dynamism and Hegel's concept of dialectics. The importance that Lotman gives to the simultaneity of different cultural codes on a same literary text is wielded as example of his resistance to the concept of "overcoming" in art. The categories of Hegelian historicism would not be useful to describe phenomena of cultural simultaneity which Lotman explains with concepts as creolization and half-breedness. A posterior comparison between Lotman's and Freud's interpretations of culture -linked by and identical concem for the remains of past- allows to explain some aspects of the dynamic theory of culture such as the Russian thinker reformulated it in his last works.
Keywords: Iuri Lotman; philosophy of history